Blended Learning Integrated with Project-Based Learning: Its Effect on Learning Outcomes, Perception, and Self-Regulated Learning - Lisa Pohan; Julia Maulina (Jurnal Pendidikan Kimia Indonesia, 2022)
The demands on chemistry learning require hands-on action in the form of practicums to fit understanding of chemical concepts, examine the theories obtained and relate them to everyday scientific phenomena through scientific activities in the laboratory. So that cognitive, affective, and psychomotor learning outcomes are achieved. This research is a type of qualitative descriptive research. This study investigates student perceptions and Self-Regulated Learning (SRL) on integrated blended learning Project Based Learning that affects student learning outcomes. The research subjects were nine people students who were enrolled in basic chemistry courses. This research was conducted for seven meetings where the learning process was carried out with a mixture of online and offline lectures called Blended Learning. Data collection was conducted through interviews to determine student perceptions of Blended Learning and a questionnaire to determine the student's SRL level. Learning Outcomes (LO) tests were in the form of cognitive, affective, and psychomotor. The interview data were analyzed inductively. Meanwhile, the SRL data analysis and the LO test are presented as an integrated and comparative description. Students' interviews revealed positive perceptions about the learning. This study found that the students' SRL were in the high (56%), medium (33%), and low (11%) categories. The LO assessment was obtained from the pre-test and post-test; all students' scores increased. As for the attitude, the measurements showed four categories: very good (67%), good (11%), adequate (11%), and poor (11%). Assessment of instruments designed showed that 67% of the instruments were developed while another 33% were underdeveloped.